Civil Law Aspects in the Case of Negligence of Tourism Service Providers That Result in Losses for Tourists - Junaidi, Junaidi; Fransisco, Wawan; Suharto, Bambang (Jurnal Hukum dan Keadilan, 2025)
The tourism industry in Indonesia has a vital role in the country's economy, but there are still significant problems related to the negligence of service providers that are detrimental to tourists. This study aims to analyze the application of civil law in dealing with the negligence of tourism service providers and evaluate the existing dispute resolution mechanisms. Using a normative-empirical approach, the study found that although consumer protection regulations are already in place, their implementation is still hampered by weak oversight and a lack of legal awareness among tourists. In addition, service providers often use exaggeration clauses that are detrimental to consumers. The study also identified that dispute resolution mechanisms, both litigation and non-litigation, still face various obstacles, such as lengthy procedures and high costs. Therefore, this study recommends strengthening supervision of tourism service providers, as well as reforms in the dispute resolution system by introducing mediation and arbitration as more efficient and cheaper alternatives. In addition, broader legal education to the public regarding their rights as tourism consumers is also considered important to improve legal protection for tourists in Indonesia.